(untitled) (Journal of Innovation in Academia, 2025)
The study analyzes the performance culture of the Magar living in Chitwan. Their culture is growing as hybrid form with mixing of the entities of global and local culture. Main concern of this study is related to the issue why and how performance culture of Chitwan’s Magar in-between of local and global culture. Qualitative research design was used to analyze the issue raises in the paper. Both primary and secondary sources of data were used and conclusion has based on the interpretation and analysis of the collected data. It is found that due to influence technology, migration , influences of mass commutation and social media, demand of tourism play role to adopt global culture and issue of self-recognition, self-dignity and indigenous feeling of pride force to continue and preserve their native cultural value and practice.